“Masjid Kapal” Tourism Destination as Estetic Expression Media of Semarang City Society - Firdaus Perdana; Hendri Hermawan Adinugraha; Mila Sartika (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2020)
The purpose of this study is to describe the tourist destination “Masjid Kapal” as a medium for aesthetic expression of the people of Semarang City. This study used a qualitative method with an interactive model consisting of three activities, namely data reduction, data presentation and verification. The results of the study concluded that the establishment of the “Masjid Kapal” in Podorejo village has a large enough potential as a religious tourism destination in the city of Semarang. “Masjid Kapal” is also an alternative choice of religious tourism in the city of Semarang. The architectural art of “Masjid Kapal” as an aesthetic expression of the people of Semarang City can be found through the uniqueness of mosque architecture and the beauty of its ornaments. The symbolic aesthetic shows that mosque managers and visitors view the “Masjid Kapal” as a place of worship as well as a tourist destination in the city of Semarang.